1995
DOI: 10.1007/s001250050318
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of IDDM during 1988?1992 in Zagreb, Croatia

Abstract: SummaryThe objective of this study was to determine the incidence of insulin-dependent diabetes mellitus (IDDM) in the population of Zagreb, Croatia, during 1988Croatia, during -1992. A centralized diabetes registry was the primary source of data, while secondary sources were used to assess ascertainment. A total of 282 new cases of IDDM were diagnosed in the study period, the primary and secondary sources identifying annually 93-100 % of the cases. The annual incidence rate ranged from 5.6 per 100,000 to 6.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…However, in the age-group 15-39 years, the incidence rates decrease with age in females older than age 15, but not in males, resulting in twofold higher incidence rate in males than in females. This sex-dependent difference in risk in older age-groups has also been observed in other countries with an intermediate or high risk (Croatia [13], Italy [Turin {16}], Norway [17], Sardinia [18], Spain [19], Sweden [23], Denmark [14]), but not in regions with a low risk (Barbados [20], Poland [21], Pavia [22]). It may be caused by the effect of sex hormones as well as by lifestyle factors, such as obesity, physical activity, and diet, as recently shown for NIDDM (38).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, in the age-group 15-39 years, the incidence rates decrease with age in females older than age 15, but not in males, resulting in twofold higher incidence rate in males than in females. This sex-dependent difference in risk in older age-groups has also been observed in other countries with an intermediate or high risk (Croatia [13], Italy [Turin {16}], Norway [17], Sardinia [18], Spain [19], Sweden [23], Denmark [14]), but not in regions with a low risk (Barbados [20], Poland [21], Pavia [22]). It may be caused by the effect of sex hormones as well as by lifestyle factors, such as obesity, physical activity, and diet, as recently shown for NIDDM (38).…”
Section: Discussionmentioning
confidence: 69%
“…The present data indicate that the incidence rate of IDDM among adult diabetic patients is higher than previously expected. Meta-analysis of data from other regional and national diabetes registries studying the diabetic population above age 15 years (Denmark [8], Croatia [13], Italy [Turin (15,16), Pavia (22)], Sardinia [18], Spain [19], Poland [21]) has already revealed this notion. Although data are not yet available, it is conceivable that a comparable number of IDDM patients become clinically overt above the age of 40 years.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…All studies were published between 1992 and 2018, with thirty-three published since 2011. Thirty-eight studies reported on populations affected by armed conflict, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] two reported on populations affected by natural disasters, 34,37 and one on all crisis types. 26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25]…”
Section: Existing Evidencementioning
confidence: 99%
“…26,37 Twenty-five studies addressed refugee populations, [17][18][19][20][21]25,26,[29][30][31]33,35,[39][40][41][42][43]47,48,50,[52][53][54][55]57 five addressed IDPs, 22,28,32,46,56 and eleven addressed non-displaced conflict-affected populations. 23,24,27,34,[36][37][38]44,45,49,51 The majority of studies were conducted in the WHO Eastern Mediterranean (N=30), [17][18][19][20][21][22][23][24][28]…”
Section: Existing Evidencementioning
confidence: 99%